PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR SIMULASI DIGITAL SISWA KELAS X TAV SMKN 2 GUNUNG TALANG - Richi Yuliani; Hanesman Hanesman; Almasri Almasri (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2017)
The problem in this study is the low average learning outcomes of learners in the subjects of Digital Simulation is under Minimum Criteria of completeness (KKM) which has been established SMKN 2 Mount Talang is 75. This study aims to determine the influence of cooperative learning model type Numbered Heads Together with direct learning model on student learning outcomes in Digital Simulation subjects students Audio Video Engineering at SMKN 2 Mount Talang. The type of this research is experimental research with the design of quasy-experiment with Posttest-Only Control Design design. The research sample is class X TAV 2 as experiment class using cooperative learning model type Numbered Heads Together and class X TAV 1 as control class using direct learning model. Data collection techniques from post-test in the experimental class and control class, then analyzed for homogeneity test, normality test and hypothesis test. From the experimental class research results obtained an average value of 81.15, while the control class get an average value of 76.50. Result of hypothesis calculation at significant level α = 0,05 got titung> ttable that is 3.05> 2.02, because big tcount of ttable, null hypothesis (H0) rejected and alternative hypothesis (Ha) accepted. Can be concluded mean at the real level, this research show that, there is influence of student learning result which signifikan between use of model of cooperative learning model type Numbered Heads Together with direct instruction model on Digital Simulation subject of class X student Audio Video Technique at SMKN 2 Gunung Talang. So the model of learning Numbered Heads Together better in comparison with direct learning model. Keywords: Numbered Heads Together, direct learning model, quasy experimental, learning outcome, eksperimen, control